Model Pendidikan Moderat di Pondok Pesantren: Studi Multisitus di Pondok Pesantren Sidogiri Kraton Pasuruan dan Pondok Pesantren Al Anwar Modung Bangkalan: Penelitian - Ahmad Atha’illah; Maftuh (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Islamic boarding schools (pondok pesantren) are Islamic educational institutions that play a crucial role in shaping religious and social character, aiming to cultivate individuals with noble character who bring benefit to all of creation. This study aims to examine the implementation of the moderate Islamic education model at Sidogiri Islamic Boarding School and Al-Anwar Islamic Boarding School, identify differences in their approaches, analyze the impacts on students and the surrounding community, and explore the challenges faced in its development. This research employed a qualitative descriptive approach with a multisite research design, in which data were obtained through observation and documentation, then analyzed descriptively and interpreted with the support of relevant theories. The findings reveal that both institutions implement moderate Islamic education through learning modules, extracurricular activities, and daily practices that instill anti-violence values, preserve local culture, and foster national commitment. The difference lies in Sidogiri Islamic Boarding School maintaining a strong adherence to traditional salaf values, whereas Al-Anwar Islamic Boarding School integrates salaf traditions with formal education. The impact can be seen in the positive responses from students and their parents toward the provided guidance. The challenges faced include diverse cultural backgrounds that are not always aligned, requiring proper management and structuring so that the teachings can be well accepted and understood.